1984
DOI: 10.1038/311477a0
|View full text |Cite
|
Sign up to set email alerts
|

42,000-molecular weight EGF receptor has protein kinase activity

Abstract: The epidermal growth factor (EGF) receptor and other growth factor receptors have been shown to possess tyrosine-specific protein kinase activity. Before the demonstration of kinase activity in growth factor receptors, tyrosine kinases of molecular weight (MW) 60,000 (60K) were found to be encoded by the src oncogene and other oncogenes related to src. Our earlier work on intracellular processing of the EGF receptor, a 170,000-MW polypeptide, provided evidence for proteolytic separation of well defined structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

1985
1985
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 19 publications
2
39
1
Order By: Relevance
“…Like the holoenzyme, the cytoplasmic domain of the EGF-R was highly active in the presence of Mn2+, but showed little activity in the presence of Mg2+. Limited proteolytic digestion of the EGF-R holoenzyme results in the generation of a 42-kDa tyrosine kinase domain fragment with protein-tyrosine kinase activity (Koland and Cerione, 1990;Basu et al, 1984). This fragment has been reported to be catalytically active only in the presence of Mn2+.…”
Section: Discussionmentioning
confidence: 99%
“…Like the holoenzyme, the cytoplasmic domain of the EGF-R was highly active in the presence of Mn2+, but showed little activity in the presence of Mg2+. Limited proteolytic digestion of the EGF-R holoenzyme results in the generation of a 42-kDa tyrosine kinase domain fragment with protein-tyrosine kinase activity (Koland and Cerione, 1990;Basu et al, 1984). This fragment has been reported to be catalytically active only in the presence of Mn2+.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of a functional gene product was dcmonstrated by means of a protein kinase assay. This confirins the previous observation [3] that this region of the EGF receptor retains catalytic activity even after deletion of the EGF-binding region, transmembrane domain and autophosphorylation sites, and also shows that it is possible to express active human EGF-receptor protcin kinase domain protein in E. coli.…”
Section: U1-u4mentioning
confidence: 60%
“…Based on the complete amino acid sequence deduced from the nucleotide sequences of cDNA clones [2], it was shown that the receptor consists of an extracellular EGF-binding domain, a hydrophobic transmembrane segment, a cytoplasmic domain which has a catalytic portion possessing tyrosine kinase activity [3] and several autophosphorylation sites. The kinase can mediate autophosphorylation, phosphorylate a variety of other proteins and is activated by EGF-binding.…”
mentioning
confidence: 99%
“…Tyr992, known to associate with phospholipase Cy, is a likely phosphorylation site candidate, though the phosphorylated residue in the 42-kDa kinase has not been identified. A similar, catalytically active, 42-kDa fragment has been isolated in v i m by tryptic digestion of intact EGF receptor (Basu et al, 1984;Koland and Cerione, 1990). Although the N-terminus of the tryptic fragment has not been identified, it has been suggested to be C-terminal to Thr6.54 (Koland and Cerione, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Accessibility Of this region to several proteases suggested that it is relatively exposed (Basu et al, 1984;Hunter, 1984;Gates and King, 198.5 …”
Section: Discussionmentioning
confidence: 99%